Effect of Bicyclopyrone on Triploid Watermelon in Plasticulture. (21st June 2018) - Bertucci, Matthew B.; Jennings, Katherine M.; Monks, David W.; Jordan, David L.; Schultheis, Jonathan R.; Louws, Frank J.; Waldschmidt, Matthew D.
Abstract: Field studies were conducted to determine watermelon tolerance and yield response when treated with bicyclopyrone preplant (PREPLANT), POST, and POST-directed (POST-DIR). Treatments consisted of two rates of bicyclopyrone (37.5 and 50 g ai ha –1 ), fomesafen (175 g ai ha –1 ), S -metolachlor (802 g ai ha –1 ), and a nontreated check. Preplant treatments were applied to formed beds 1 d prior to transplanting and included bicyclopyrone (37.5 and 50 g ha –1 ) and fomesafen (175 g ha –1 ), and new polyethylene mulch was subsequently laid above treated beds. POST and POST-DIR treatments were applied 14 ± 1 d after watermelon transplanting and included bicyclopyrone (37.5 and 50 g ha –1 ) POST and POST-DIR, and S -metolachlor (802 g ai ha –1 ) POST-DIR. POST-DIR treatments were applied to row middles, ensuring that no herbicide contacted watermelon vines or polyethylene mulch. At 2 wk after transplanting (WAT), 15% foliar bleaching was observed in watermelon treated with bicyclopyrone (50 g ha –1 ) PRE. At 3 WAT, bicyclopyrone (37.5 and 50 g ha –1 ) POST caused 16% and 17% foliar bleaching and 8% and 9% crop stunting, respectively. At 4 WAT, initial injury had subsided and bicyclopyrone (37.5 and 50 g ha –1 ) POST caused 4% and 4% foliar bleaching and 4% and 8% crop stunting, respectively. No symptoms of bleaching or stunting were observed at 6- and 8-WAT ratings. Watermelon total yield, marketable yield, total fruit number, marketable fruit number, and average fruit size were unaffected by herbicide treatments. Therefore, registration of bicyclopyrone (37.5 and 50 g ha –1 ) PREPLANT, POST, and POST-DIR would offer watermelon producers a safe herbicide option and a novel mode of action for weed management.